CHARACTERISTIC OF PRASEODYMIUM OXIDE BASED CATALYST IN METHANATION: EFFECT CALCINATION TEMPERATURE - Salmiah Jamal Mat Rosid; Susilawati Toemen; Wan Azelee Wan Abu Bakar a; Sarina Mat Rosid; Wan Nazwanie Wan Abdullah; Siti Maisarah Aziz (Journal of Academia, 2021)
Methanation reaction using carbon dioxide gas is one of favorable green technology to form methane gas by converting carbon dioxide in the presence of hydrogen. This technology needs the catalyst to achieve a higher catalytic activity. Therefore, a catalyst of Ru/Mn/Pr (5:30:65)/Al2O3 (RMP, 5:30:60) was prepared via wetness impregnation method and investigated on the effect of calcination temperatures with respect to catalytic performance using FTIR analysis. The RMP (5:30:60) catalyst calcined at 800oC was chosen as an excel catalyst with 96.9% of CO2 conversion and 45.1% CH4 formation at 350oC reaction temperature. From the EDX mapping, it can be observed that the distribution of all element is homogeneous at 800oC except Ru, O and Al at 900oC and 1000oC calcination temperature. The image from FESEM also shows the presence of some crystal shape on the catalyst surface. From the FTIR analysis, the peaks stretching and bending mode of O-H bonding decreased when the calcination temperature increased.